Pengaruh Variasi Dimensi Sirip Pada Displacer Sistem Pendingin Mesin Stirling Menggunakan Energi Surya Terkonsentrasi - Moch. Zainul Achyak; Purbo Suwandono; Gatot Soebiyakto (Jurnal Energi dan Teknologi Manufaktur, 2022)
Energy needs in Indonesia are increasing day by day due to population growth and economic growth. To meet the increasing energy needs, it is necessary to develop a variety of alternative energies such as: biomass, solar energy, wind energy, water energy, which are still few that utilize One of the machines that use renewable energy is the Stirling motor. A stirling motor is a type of motor that has an external combustion engine that does not require much maintenance and does not emit a lot of pollutants because it only requires a source of thermal energy to run it. In other words, solar energy can also be utilized. The method developed is the use of solar energy which is concentrated by a parabolic reflector to the hot cylinder of the Stirling engine to convert heat energy into motion energy. The purpose of this study was to determine the effect of variations of several fin dimensions and variations in the number of fins on a displacer with aluminum material. This study uses an experimental method to describe the performance of the stirling engine prototype using various dimensions of cooling fins and variations in the number of fins. The results showed that the gamma stirling engine using 6 fins, and a diameter of 38 mm, showed the best results with a time of 43 minutes with an intensity of solar radiation of 188.2 W/m² to drive the stirling engine with a speed of 189 rpm and a torque of 0.87 N. mm. The difference in temperature produced in the hot cylinder and cold cylinder is 115˚C with a thermal efficiency of 44.13%.